Evaluasi Pembelajaran Jarak Jauh Dalam Jaringan Mata Kuliah Berbicara Bahasa Mandarin - Trihardini, Ayu (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
In the midst of teachers and students’ effort to adapt to the era of technological disruption and global competition, the Covid-19 pandemic has become a catalyst for learning models changing all over the world. The Chinese Language Education Study Program, Faculty of Language and Arts, State University of Jakarta (PSPBM FBS UNJ) is also developing online distance learning. This paper mainly discusses the evaluation of the implementation of online distance learning for speaking skills at PSPBM UNJ, including the learning media used, the obstacles faced and how online distance learning affects the motivation of students. This study uses quantitative and qualitative methods through surveys and qualitative analysis in the discussion. Respondents are students and lecturers of PSPBM. This evaluation research is the basis for further research on the development of an online distance learning model for Chinese language speaking skills. The results of this research can be integrated into consideration for policy makers in determining the policies needed to improve the quality of learning; can also be a very important input for course instructors so that they can think more creatively and provide solutions in realizing interesting, efficient, and useful lecture activities for students; as well as being input and consideration for the general public who are related to online distance learning in determining the various attitudes needed to improve the quality of online distance learning.